Findings from local consultations on resilience in Makueni County - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
The Overseas Development Institute (ODI) has convened a consortium that includes the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS), the Kenya Red Cross Society (KRCS), the Kenya National Drought Management Authority (NDMA) and others to respond to a call for proposals by the Global Resilience Partnership. The project envisaged by the consortium is named ‘Dialling Up resilience: Mobilising ICTs to enhance bottom-up resilience measurement, programming and governance in the Horn of Africa’. The project is based on the belief that better measurement and tracking of resilience are key to ensuring that investments in resilience building are supporting the right activities and targeting the right people. In this context, CCAFS and KRCS, with the help of NDMA officials in Makueni County, organized community consultations to learn about how household resilience is conceptualized at the local level. Staff from CCAFS and KRCS trained KRCS volunteers to conduct focus group discussions (FGDs) and household case studies. The volunteers visited two communities in Makueni County between 24 June and 1 July 2015. This report summarizes the findings from their field work and draws lessons from the exercise to apply to any future similar exercises.